Method for producing sintered silicon nitride
Patent Information
- Application Number
- JP2021561497
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-28
- Filing Date
- 2020-11-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-11-26
AI Technical Summary
【0013】 本発明によれば、β化率の高い窒化ケイ素粉末を用い、かつ常圧又は略常圧で焼成させる場合であっても、熱伝導率の高い窒化ケイ素焼結体を得ることができる窒化ケイ素焼結体の製造方法を提供することができる。
Smart Images

Figure 0007645813000001 
Figure 0007645813000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a silicon nitride sintered body having high thermal conductivity. [Background technology]
[0002] Silicon nitride sintered bodies, which are made by adding various sintering aids to silicon nitride powder and sintering them at high temperatures, are characterized by their light weight, high mechanical strength, high chemical resistance, high electrical insulation, etc., among various ceramic sintered bodies, and are used as wear-resistant parts such as ball bearings and high-temperature structural parts. In addition, by optimizing the type of aid and sintering conditions, it is possible to increase thermal conductivity, so they have also come to be used as thin, high-strength heat-dissipating substrate materials.
[0003] Known methods for synthesizing silicon nitride powder include the reduction nitridation method, in which silica powder is used as the raw material and nitrogen gas is passed through in the presence of carbon powder to produce silicon nitride (e.g., Patent Document 1), the direct nitridation method, in which metallic silicon (silicon powder) is reacted with nitrogen at high temperatures (e.g., Patent Document 2), and the imide decomposition method, in which silicon halide is reacted with ammonia. Furthermore, a method for synthesizing metal nitrides by a direct nitridation method using a self-propagating high temperature synthesis (SHS) method is also known. The self-propagating high temperature synthesis method is also called combustion synthesis, and is a synthesis method in which raw material powders including silicon powder are introduced into a reaction vessel, and a part of the raw material powder is ignited under a nitrogen atmosphere to cause a nitriding reaction, and the nitriding combustion heat generated by the nitriding reaction is propagated to the surroundings to cause a reaction in the entire material, and is known as a relatively inexpensive synthesis method.
[0004] It is known that silicon nitride powder has two crystal forms, α-type and β-type. For example, as shown in Non-Patent Document 1, α-type silicon nitride powder is dissolved in a sintering aid during the sintering process and reprecipitated as β-type, which results in a dense sintered body with high thermal conductivity, and is therefore currently in wide use.
[0005] However, when producing α-type silicon nitride powder, the manufacturing process tends to be complicated. For example, in the direct nitriding method, nitriding must be performed at a low temperature for a long period of time to prevent the formation of β-type, which increases the manufacturing cost (Non-Patent Document 2).
[0006] In light of this background, there is a demand for a technology for producing dense sintered bodies with high thermal conductivity using β-type silicon nitride powder, which can be produced at relatively low cost. Patent Document 3 describes an invention relating to a highly thermally conductive silicon nitride ceramic and a method for producing the same, and in the examples, it shows that a dense sintered body with high thermal conductivity can be obtained by sintering a molded body containing β-type silicon nitride powder having an average particle size of 0.5 μm and a sintering aid consisting of ytterbium oxide and magnesium silicon nitride powder at 1900°C for 2 to 24 hours in pressurized nitrogen at 10 atmospheres. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2009-161376 A [Patent Document 2] Japanese Patent Application Publication No. 10-218612 [Patent Document 3] JP 2002-128569 A [Non-patent literature]
[0008] [Non-Patent Document 1] Journal of the Japan Marine Engineering Society, September 1993, Vol. 28, No. 9, p548-556 [Non-Patent Document 2] Journal of the Ceramic Society of Japan 100
[11] 1366-1370(1992) Summary of the Invention [Problem to be solved by the invention]
[0009] The sintered body of β-type silicon nitride powder disclosed in Patent Document 3 is produced in pressurized nitrogen at 10 atmospheres as described above. In general, when sintering is performed under pressure, it is easier to suppress the decomposition of the raw material silicon nitride, and therefore it is possible to sinter at a high temperature of over 1800°C. When sintering is performed under such high temperature and pressure, the sintered body produced is more likely to be densified, and it is possible to reduce the amount of impurity oxygen dissolved inside the silicon nitride particles, which is one of the factors that reduces thermal conductivity, and it is known that a sintered body with high thermal conductivity is more likely to be obtained. However, when sintering under pressure as in Patent Document 3, it is necessary to use a pressure-resistant container during production. Therefore, there are problems with equipment restrictions in production and high production costs. Furthermore, Patent Document 3 does not describe or suggest at all a method for obtaining a sintered body with high thermal conductivity using β-type silicon nitride powder under normal pressure (atmospheric pressure) or approximately normal pressure (pressure close to atmospheric pressure) conditions that do not require the use of a pressure-resistant container.
[0010] The present invention has been made in consideration of the above-mentioned problems in the conventional technology, and has an object to provide a method for producing a sintered body having high thermal conductivity by using silicon nitride powder having a high degree of β-conversion as a raw material and sintering this at normal pressure or approximately normal pressure, which are conditions that are generally recognized as making it difficult to obtain a sintered body having high thermal conductivity. [Means for solving the problem]
[0011] The present inventors have conducted extensive research to achieve the above object, and as a result have found that a sintered body with high thermal conductivity can be obtained by using a molded body containing silicon nitride powder having a specific range of beta conversion rate, dissolved oxygen content, and specific surface area, and a sintering aid containing a compound having no oxygen bonds, and having a specific range of total oxygen content and total aluminum element content, and firing the molded body at normal pressure or approximately normal pressure within a specific temperature range, thereby completing the present invention.
[0012] The gist of the present invention is the following [1] to
[10] . [1] The β-phase ratio is 80% or more, the amount of dissolved oxygen is 0.2% by mass or less, and the specific surface area is 5 to 20 m 2 The method for producing a silicon nitride sintered body comprises heating a molded body, the molded body containing silicon nitride powder having a total oxygen content of 1 to 15 mass% and a total aluminum content of 800 ppm or less, at a temperature of 1200 to 1800°C in an inert gas atmosphere under a pressure of 0 MPa·G or more and less than 0.1 MPa·G to sinter the silicon nitride. [2] The method for producing a silicon nitride sintered body according to the above [1], wherein the total oxygen content of the silicon nitride powder is 1 mass% or more. [3] The method for producing a silicon nitride sintered body according to the above [1] or [2], wherein the molded body is obtained by molding a molding composition containing silicon nitride powder, a sintering aid, and water. [4] The silicon nitride powder has an average particle size D 50 The method for producing a silicon nitride sintered body according to any one of the above [1] to [3], wherein the average particle size is 0.5 to 1.2 μm, the proportion of particles having a particle size of 0.5 μm or less is 20 to 50 mass %, and the proportion of particles having a particle size of 1.0 μm or more is 20 to 50 mass %. [5] The method for producing a silicon nitride sintered body according to any one of the above [1] to [4], wherein the sintering aid contains a metal oxide. [6] A method for producing a silicon nitride sintered body according to any one of the above [1] to [5], wherein the compound having no oxygen bond contained in the sintering aid is a carbonitride-based compound containing a rare earth element or a magnesium element. [7] The density of the molded body is 1.95 g / cm 3 The method for producing a silicon nitride sintered body according to any one of the above [1] to [6]. [8] The method for producing a silicon nitride sintered body according to any one of the above [1] to [7], wherein the thermal conductivity of the resulting silicon nitride sintered body measured by a laser flash method is 80 W / mK or more. [9] The method for producing a silicon nitride sintered body according to any one of the above [1] to [8], wherein the resulting silicon nitride sintered body has a dielectric breakdown voltage of 11 kV or more.
[10] The method for producing a silicon nitride sintered body according to any one of the above [1] to [9], wherein the silicon nitride sintered body obtained has an Ra of 0.6 μm or less. Effect of the Invention
[0013] According to the present invention, a method for producing a silicon nitride sintered body can be provided that can produce a silicon nitride sintered body with high thermal conductivity even when silicon nitride powder with a high beta content is used and sintering is performed at normal pressure or approximately normal pressure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [Method of manufacturing sintered silicon nitride] The method for producing a silicon nitride sintered body of the present invention is a method for producing a silicon nitride sintered body having a β-phase ratio of 80% or more, a dissolved oxygen content of 0.2 mass% or less, and a specific surface area of 5 to 20 m 2 The method is characterized in that a molded body containing silicon nitride powder of 0.1 g / g and a sintering aid containing a compound having no oxygen bonds, and in which the total oxygen content is adjusted to 1 to 15 mass% and the total aluminum content is 800 ppm or less, is heated to a temperature of 1200 to 1800°C in an inert gas atmosphere under a pressure of 0.1 MPa·G or more and less than 0.5 MPa·G to sinter the silicon nitride.
[0015] [Molded body] The molded body used in the method for producing a silicon nitride sintered body of the present invention will be described below. The molded body contains a specific silicon nitride powder and a sintering aid, which will be described below.
[0016] <Silicon nitride powder> (β conversion rate) The β-phase rate of the silicon nitride powder contained in the molded body is 80% or more. Silicon nitride powder with a β-phase rate of 80% or more can be obtained without setting strict manufacturing conditions, so it can be manufactured at a relatively low cost. Therefore, by using silicon nitride powder with a high β-phase rate, the overall manufacturing cost of the silicon nitride sintered body can be reduced. In addition, by setting the β-phase rate high, the amount of oxygen taken in when the α-silicon nitride particles transform into β-silicon nitride particles during sintering can be further reduced. Here, the β-phase rate of the silicon nitride powder is preferably 85% or more, more preferably 90% or more.
[0017] The β-phase ratio of silicon nitride powder means the peak intensity ratio of the β-phase to the total of the α-phase and β-phase in the silicon nitride powder [100 × (peak intensity of the β-phase) / (peak intensity of the α-phase + peak intensity of the β-phase)], which is determined by powder X-ray diffraction (XRD) measurement using CuKα radiation. More specifically, it is determined by calculating the weight ratio of the α-phase and β-phase in the silicon nitride powder according to the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780.
[0018] (solid dissolved oxygen amount) The amount of dissolved oxygen in the silicon nitride powder is 0.2% by mass or less. If the amount of dissolved oxygen exceeds 0.2% by mass, the thermal conductivity of the silicon nitride sintered body obtained by firing under the firing conditions characteristic of the present invention will be low. From the viewpoint of obtaining a silicon nitride sintered body with high thermal conductivity, the amount of dissolved oxygen in the silicon nitride powder is preferably 0.1% by mass or less. Here, the amount of dissolved oxygen refers to the oxygen dissolved inside the particles of the silicon nitride powder (hereinafter also referred to as internal oxygen), and does not include oxygen derived from oxides such as SiO2 that are inevitably present on the particle surface (hereinafter also referred to as external oxygen). The amount of dissolved oxygen can be measured by the method described in the Examples.
[0019] The method for adjusting the amount of dissolved oxygen in silicon nitride powder is not particularly limited, but for example, when producing silicon nitride powder, it is preferable to use a high-purity raw material. For example, when producing silicon nitride powder by direct nitridation, it is preferable to use silicon powder that does not have a factor that causes oxygen to be dissolved inside as the raw material to be used, and specifically, it is preferable to use silicon powder derived from semiconductor grade silicon, for example, silicon powder represented by cutting powder generated when processing the above silicon, such as cutting. The above semiconductor grade silicon is typically polycrystalline silicon obtained by the so-called "Siemens process" in which high-purity trichlorosilane is reacted with hydrogen in a bell jar type reaction vessel.
[0020] (specific surface area) The specific surface area of silicon nitride powder is 5 to 20 m 2 / g. The specific surface area of silicon nitride powder is 20m 2 When the specific surface area exceeds 5m / g, it becomes difficult to reduce the amount of dissolved oxygen. 2 If the specific surface area is less than 7 to 20 m / g, it is difficult to obtain a silicon nitride sintered body having high density and strength. 2 / g, more preferably 12 to 15m 2 / g. In the present invention, the specific surface area means a BET specific surface area measured by a BET single point method using nitrogen gas adsorption.
[0021] (Average particle size) Average particle size of silicon nitride powder D 50 The average particle diameter D is preferably 0.5 to 3 μm, and more preferably 0.7 to 1.7 μm. When silicon nitride powder having such an average particle diameter is used, sintering proceeds more easily. 50 is a value measured by a laser diffraction scattering method on a 50% volume basis. The proportion of particles with a particle size of 0.5 μm or less in the silicon nitride powder is preferably 20 to 50 mass %, more preferably 20 to 40 mass %. The proportion of particles with a particle size of 1.0 μm or more in the silicon nitride powder is preferably 20 to 50 mass %, more preferably 20 to 40 mass %. By using silicon nitride powder having such a particle size distribution, it becomes easier to obtain a dense silicon nitride sintered body with high thermal conductivity. The reason for this is not clear, but it is thought that, unlike α-silicon nitride particles, β-silicon nitride particles are less likely to dissolve and reprecipitate during sintering, and that by maintaining a certain balance between fine and coarse particles in the early stages of sintering, it is possible to obtain a denser sintered body.
[0022] (Total oxygen) The total oxygen content of the silicon nitride powder is not particularly limited, but is preferably 1% by mass or more. The total oxygen content is the sum of the amount of dissolved oxygen (internal oxygen) and the amount of external oxygen. If the total oxygen content is equal to or greater than these lower limits, for example, the effect of facilitating sintering due to silicon oxide on the particle surface is exhibited. In addition, the total oxygen content of the silicon nitride powder is preferably 10% by mass or less. Even if the total oxygen content of the silicon nitride powder is 1 mass % or more, the thermal conductivity of the sintered body can be increased as long as the amount of dissolved oxygen is equal to or less than the above-mentioned certain value. The total oxygen content of the silicon nitride powder can be measured by the method described in the Examples.
[0023] The amount of silicon nitride powder in the molded body is preferably 80 mass % or more, and more preferably 90 mass % or more, based on the total amount of the molded body.
[0024] <Production of silicon nitride powder> The method for producing silicon nitride powder is not particularly limited as long as it can obtain silicon nitride powder having the above-mentioned characteristics.As the method for producing silicon nitride powder, for example, the reduction nitridation method of using silica powder as raw material and circulating nitrogen gas in the presence of carbon powder to generate silicon nitride, the direct nitridation method of reacting silicon powder with nitrogen at high temperature, the imide decomposition method of reacting silicon halide with ammonia, etc. can be applied, but from the viewpoint of easy production of silicon nitride powder having the above-mentioned characteristics, the direct nitridation method is preferred, and among them, the direct nitridation method (combustion synthesis method) using self-combustion method is more preferred. The combustion synthesis method uses silicon powder as a raw material, forcibly ignites a part of the raw material powder under a nitrogen atmosphere, and synthesizes silicon nitride by self-heating of the raw material compound. The combustion synthesis method is a known method, and reference can be made to, for example, JP 2000-264608 A, WO 2019 / 167879, etc.
[0025] <Sintering aid> The molded body of the present invention contains a sintering aid containing a compound having no oxygen bonds. By using such a sintering aid, it is possible to prevent a decrease in the thermal conductivity of the resulting silicon nitride sintered body. As the compound having no oxygen bond, a carbonitride-based compound containing a rare earth element or magnesium element (hereinafter, also referred to as a specific carbonitride-based compound) is preferable. By using such a specific carbonitride-based compound, it becomes easier to obtain a silicon nitride sintered body having high thermal conductivity more effectively. Although the reason for this is not clear, it is presumed that the specific carbonitride-based compound functions as a getter agent that adsorbs oxygen contained in the silicon nitride powder, and as a result, a silicon nitride sintered body having high thermal conductivity is obtained.
[0026] In the carbonitride-based compound containing a rare earth element, the rare earth element is preferably Y (yttrium), La (lanthanum), Sm (samarium), Ce (cerium), or the like.
[0027] Examples of carbonitride compounds containing rare earth elements include Y2Si4N6C, Yb2Si4N6C, Ce2Si4N6C, etc., and among these, Y2Si4N6C and Yb2Si4N6C are preferred from the viewpoint of facilitating the production of a silicon nitride sintered body having high thermal conductivity. An example of a magnesium-containing carbonitride compound is MgSi4N6C. These specific carbonitride compounds may be used alone or in combination of two or more.
[0028] Among the above carbonitride compounds containing rare earth elements or magnesium element, particularly preferred compounds are Y2Si4N6C and MgSi4N6C.
[0029] In addition to the compound having no oxygen bond, the sintering aid may further contain a metal oxide. When the sintering aid contains a metal oxide, the sintering of the silicon nitride powder is facilitated, and a denser and stronger sintered body can be obtained. Examples of metal oxides include yttria (Y2O3), magnesia (MgO), and ceria (CeO). Among these, yttria is preferable. The metal oxides may be used alone or in combination of two or more.
[0030] The mass ratio of the oxygen-free compound, typified by the specific carbonitride-based compound, to the metal oxide contained in the sintering aid (oxygen-free compound / metal oxide) is preferably 0.2 to 4, and more preferably 0.6 to 2. Within this range, a dense silicon nitride sintered body with high thermal conductivity can be easily obtained.
[0031] The content of the sintering aid in the compact is preferably 5 to 20 parts by mass, and more preferably 7 to 10 parts by mass, based on 100 parts by mass of the silicon nitride powder.
[0032] <Binder> The molded body can be molded using a binder. In this case, the molded body can be obtained by molding a molding composition described later, and optionally drying and degreasing the molded body to remove the binder. The binder is not particularly limited, but examples thereof include polyvinyl alcohol, polyvinyl butyral, methyl cellulose, alginic acid, polyethylene glycol, carboxymethyl cellulose, ethyl cellulose, and acrylic resins.
[0033] The content of the binder in the molding composition used to produce the molded body is preferably 1 to 30 parts by mass per 100 parts by mass of the silicon nitride powder, and the ratio may be appropriately determined depending on the molding method.
[0034] <Total oxygen amount> In the present invention, the total oxygen content of the molded body is 1 to 15% by mass. Here, as can be understood from the above explanation, the molded body refers to a state in which it is to be sintered, and does not include binders, solvents, etc. used in the production of the molded body, which are removed by treatments such as drying and degreasing before being sintered. If the total oxygen content exceeds 15% by mass, the thermal conductivity of the resulting silicon nitride sintered body decreases due to the influence of oxygen. Also, if the total oxygen content is less than 1% by mass, sintering is difficult to proceed, a dense silicon nitride sintered body cannot be obtained, and the thermal conductivity and strength decrease. The total oxygen content of the molded body is preferably 2 to 10% by mass, more preferably 3 to 5% by mass. The total oxygen content can be set to a desired range by appropriately adjusting the total oxygen content of the silicon nitride used, the type of sintering aid, and the molding method.
[0035] <Total aluminum content> The total aluminum element content (mass) of the molded body is 800 ppm or less. That is, the molded body used in the present invention has a very small amount of aluminum element, which makes it possible to obtain a silicon nitride sintered body having high thermal conductivity. The total aluminum element content of the molded body is preferably 500 ppm or less, more preferably 200 ppm or less.
[0036] <Molded object density> The density of the molded body is not particularly limited, but is preferably 1.95 g / cm 3 More preferably, it is 1.98 g / cm 3 When the density of the molded body is equal to or greater than these lower limits, it becomes easier to obtain a silicon nitride sintered body having excellent thermal conductivity.
[0037] [Production of Molded Product] The method for producing the molded body used in the present invention is not particularly limited, and examples thereof include a method in which a molding composition containing at least silicon nitride powder and a sintering aid is molded by a known molding method, such as press molding, extrusion molding, injection molding, and sheet molding (doctor blade method).
[0038] From the viewpoint of ease of molding, the molding composition may further contain a binder, the types of which are as described above. The amounts of sintering aid and binder per 100 parts by mass of silicon nitride powder in the molding composition are the same as those explained for the molded body.
[0039] The molding composition may contain a solvent from the viewpoint of ease of handling and molding. The solvent is not particularly limited, and examples thereof include organic solvents such as alcohols and hydrocarbons, and water. In the present invention, however, it is preferable to use water. That is, it is preferable to obtain a molded body by molding a molding composition containing silicon nitride powder, a sintering aid, and water. When water is used as a solvent, it is preferable because it reduces the environmental load compared to when an organic solvent is used.
[0040] In general, when water is used as a solvent contained in a molding composition, oxygen derived from water is likely to remain inside the silicon nitride sintered body obtained by firing the molded body, and therefore the thermal conductivity is likely to decrease. In contrast, in the present invention, even if the total oxygen amount increases by using water as a solvent by using a silicon nitride powder having a solid solution oxygen amount of a certain value or less, a sintered body with high thermal conductivity can be obtained by controlling the total oxygen amount.
[0041] [Sintering method] In the method for producing sintered silicon nitride of the present invention, the above-mentioned molded body is fired under certain conditions to sinter silicon nitride. The firing conditions are described below. The firing is carried out in an inert gas atmosphere, which means, for example, a nitrogen atmosphere or an argon atmosphere.
[0042] Furthermore, in such an inert gas atmosphere, firing is carried out under a pressure of 0 MPa·G or more and less than 0.1 MPa·G. The pressure is preferably 0 MPa·G or more and 0.05 MPa·G or less, and more preferably 0 MPa·G (i.e. normal pressure (atmospheric pressure)). Here, the "G" at the end of the pressure unit MPa·G stands for gauge pressure. Generally, at atmospheric pressure or pressures in the near atmospheric pressure range, silicon nitride is easily decomposed, and therefore the temperature cannot be adjusted to, for example, above 1800°C, making it difficult to obtain a densified silicon nitride sintered body with high thermal conductivity. In contrast, the manufacturing method of the present invention uses a specific molded body as described above, and therefore a silicon nitride sintered body with high thermal conductivity can be obtained even within the above pressure range.
[0043] In addition, since silicon nitride can be sintered under normal or nearly normal pressure conditions, there is no need to manufacture it in a pressure vessel (pressure-resistant vessel). This makes it possible to simplify the manufacturing equipment and reduce manufacturing costs. Specifically, sintering can be performed in a batch furnace such as a muffle furnace or a tubular furnace, or in a continuous furnace such as a pusher furnace, allowing a variety of manufacturing methods to be applied and improving productivity.
[0044] The molded body is sintered by heating to a temperature of 1200 to 1800° C. If the temperature is less than 1200° C., sintering of silicon nitride will not proceed easily, and if it exceeds 1800° C., silicon nitride will be easily decomposed. From this viewpoint, the heating temperature during sintering is preferably 1600 to 1800° C. The firing time is not particularly limited, but is preferably about 3 to 20 hours.
[0045] When a binder is used to form the molded body, it is preferable to remove organic components such as the binder by providing a degreasing step. The degreasing conditions are not particularly limited, but for example, the molded body may be heated to 450 to 650°C in air or in an inert atmosphere such as nitrogen or argon.
[0046] [Physical properties of sintered silicon nitride] The silicon nitride sintered body obtained by the production method of the present invention exhibits high thermal conductivity, preferably 80 W / mK or more, and more preferably 100 W / mK or more. The thermal conductivity can be measured by a laser flash method.
[0047] The dielectric breakdown voltage of the silicon nitride sintered body obtained by the production method of the present invention is preferably 11 kV or more, more preferably 13 kV or more. A silicon nitride sintered body having such a dielectric breakdown voltage is unlikely to undergo dielectric breakdown, and has excellent reliability as a product.
[0048] The silicon nitride sintered body obtained by the manufacturing method of the present invention is sintered under mild conditions (at normal or nearly normal pressure and at a lower temperature than usual), and therefore has little surface irregularities. Specifically, the Ra (arithmetic mean roughness) of the obtained silicon nitride sintered body is preferably 0.6 μm or less, more preferably 0.55 μm or less. The silicon nitride sintered body having such an Ra has good adhesion to the object of use, such as metal. Furthermore, the working time when mirror-polishing the silicon nitride sintered body as necessary can be shortened. Ra can be measured by a surface roughness tester. The thermal conductivity, dielectric breakdown voltage and Ra are measured after the surface of the silicon nitride sintered body is subjected to a blasting treatment to remove any adherent substances such as a release agent that have adhered to the sintered body during sintering. EXAMPLES
[0049] EXAMPLES The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, various physical properties were measured by the following methods.
[0050] (1) Beta content of silicon nitride powder The β-phase ratio of the silicon nitride powder was determined by powder X-ray diffraction (XRD) measurement using CuKα radiation. Specifically, the weight ratio of the α-phase and β-phase of the silicon nitride powder was calculated by the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780, to determine the β-phase ratio.
[0051] (2) Specific surface area of silicon nitride powder The specific surface area of the silicon nitride powder was measured using a BET method specific surface area measuring device (Macsorb HM model-1201) manufactured by Mountec Co., Ltd., by the BET single point method using nitrogen gas adsorption. Prior to carrying out the above-mentioned specific surface area measurement, the silicon nitride powder to be measured was heat-treated in air at 600° C. for 30 minutes to remove any organic matter adsorbed on the powder surface.
[0052] (3) Amount of dissolved oxygen and total oxygen in silicon nitride powder The amount of dissolved oxygen in the silicon nitride powder was measured by inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (HORIBA Corp., "EMGA-920"). As a sample, 25 mg of the silicon nitride powder used in each Example and Comparative Example was enclosed in a tin capsule (LECO Tin Cupsule was used for the tin capsule) and introduced into a graphite crucible, heated at 5.5 kW for 20 seconds, degassed the adsorbed gas, and then heated at 0.8 kW for 10 seconds, and then from 0.8 kW to 4 kW over 350 seconds. The amount of carbon dioxide generated during this period was measured and converted into oxygen content. During the 350-second temperature rise, the oxygen generated early on corresponds to oxygen (external oxygen) derived from oxides present on the surface of silicon nitride particles, and the oxygen generated later corresponds to dissolved oxygen (internal oxygen) that is dissolved in silicon nitride crystals. Therefore, a perpendicular line was drawn from the part corresponding to the valley of these two measurement peaks, from which the background measured in advance was subtracted, to separate the two peaks. The amount of dissolved oxygen (internal oxygen) and the amount of external oxygen were calculated by proportionally allocating the areas of the respective peaks.
[0053] (4) Particle size of silicon nitride powder (i) Sample pretreatment As a pretreatment of the silicon nitride powder sample, the silicon nitride powder was calcined in air at a temperature of about 500°C for 2 hours. The calcination treatment may cause a particle size measurement in which the silicon nitride powder has a low surface oxygen content or the particle surface is covered with a hydrophobic substance due to a grinding aid during grinding, making the particles themselves hydrophobic. In such cases, dispersion in water may be insufficient, making it difficult to measure particle size reproducibly. Therefore, by calcining the silicon nitride powder sample in air at a temperature of about 200°C to 500°C for several hours, the silicon nitride powder is made hydrophilic, making it easier to disperse in water solvents and enabling highly reproducible particle size measurements. It has been confirmed that calcination in air has almost no effect on the particle size measured.
[0054] (ii) Particle size measurement 90 ml of water and 5 ml of sodium pyrophosphate with a concentration of 5% by mass were placed in a beaker (inner diameter 60 mmφ, height 70 mm) with a maximum marked capacity of 100 ml and stirred well, after which an earpick-sized amount of silicon nitride powder sample was added and the silicon nitride powder was dispersed for 2 minutes at AMPLITUDE 50% (approximately 2 amperes) using an ultrasonic homogenizer (Nippon Seiki Seisakusho US-300E, tip diameter 26 mm) The tip of the tip was inserted into the beaker up to the 20 ml mark during dispersion. Next, the particle size distribution of the obtained silicon nitride powder dispersion was measured using a laser diffraction / scattering particle size distribution measurement device (Microtrac MT3300EXII manufactured by Microtrac-Bell Co., Ltd.). The measurement conditions were as follows: water (refractive index 1.33) was selected as the solvent, refractive index 2.01 as the particle characteristics, transparent as the particle transparency, and non-spherical as the particle shape. The particle size at which the cumulative curve of the particle size distribution measured in the above particle size distribution measurement is 50% is defined as the average particle size (average particle size D50).
[0055] (5) Total oxygen content of the molded body The total oxygen content of the molded body was measured by inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (HORIBA Corp., "EMGA-920"). As a sample, 15 mg of the molded body was placed in a tin capsule (LECO Tin Capsule was used for the tin capsule), introduced into a graphite crucible, heated at 5.5 kW for 20 seconds, and then heated at 5.0 kW for another 20 seconds to degas the adsorbed gases. After that, the sample was heated at 5.0 kW for 75 seconds, and the amount of carbon dioxide generated during this period was measured and converted into oxygen content.
[0056] (6) Density of the green body The density of each molded body was measured using an automatic specific gravity meter (DMA-220H type, manufactured by Shinko Denshi Co., Ltd.), and the average value of 15 pieces was recorded as the density of the molded body.
[0057] (7) Total aluminum content of the molded body The total content of aluminum element in the molded body was measured using an inductively coupled plasma optical emission spectrometer ("iCAP 6500 DUO" manufactured by Thermo Fisher Scientific).
[0058] (8) Thermal conductivity of sintered silicon nitride The thermal conductivity of the silicon nitride sintered body was measured by the laser flash method using a Kyoto Electronics Manufacturing Co., Ltd. LFA-502. Thermal conductivity is calculated by multiplying the thermal diffusivity, sintered body density, and sintered body specific heat. The specific heat of the silicon nitride sintered body was set to 0.68 (J / g K). The sintered body density was measured using an automatic hydrometer (Shinko Denshi Co., Ltd.: DMA-220H type). The thermal conductivity was measured after the surface of the silicon nitride sintered body was blasted, and then coated with Au and carbon.
[0059] (9) Dielectric breakdown voltage of sintered silicon nitride The dielectric breakdown voltage was measured according to JIS C2110. Specifically, a voltage was applied to the silicon nitride sintered body using a dielectric strength measuring device ("TK-O-20K" manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.), and the voltage at which dielectric breakdown occurred was measured.
[0060] (10) Ra (arithmetic mean roughness) of sintered silicon nitride The Ra of the silicon nitride sintered body was measured using a surface roughness measuring instrument (Tokyo Seimitsu Co., Ltd., "Surfcom 480A") by scanning a needle with an evaluation length of 2.5 mm at a measurement speed of 0.3 mm / s. The silicon nitride sintered body used had its surface subjected to blasting treatment to remove any releasing agent or the like.
[0061] In each of the examples and comparative examples, the following raw materials were used. <Silicon nitride powder> Silicon nitride powders A, B, and C shown in Table 1 were prepared by the following method.
[0062] (Production of silicon nitride powder A) Silicon powder (semiconductor grade, average particle size 5 μm) was mixed with silicon nitride powder (average particle size 1.5 μm) as a diluent to obtain a raw material powder (Si: 80 mass%, Si3N4: 20 mass%). The raw material powder was filled into a reaction vessel to form a raw material powder layer. Next, the reaction vessel was placed in a pressure-resistant sealed reactor equipped with an ignition device and a gas supply and exhaust mechanism, and the reactor was depressurized to degas, and then nitrogen gas was supplied to replace the nitrogen. Thereafter, nitrogen gas was gradually supplied to increase the pressure up to 0.7 MPa. The bulk density of the raw material powder at the time when the predetermined pressure was reached (at the time of ignition) was 0.5 g / cm. 3 It was. Then, the end of the raw material powder in the reaction vessel was ignited, and a combustion synthesis reaction was carried out to obtain a lump product made of silicon nitride. The obtained lump product was crushed by rubbing against each other, and then an appropriate amount was put into a vibration mill and finely pulverized for 6 hours. The fine pulverizer and fine pulverization method used were of the usual type, but the inside of the pulverizer was lined with urethane as a measure to prevent heavy metal contamination, and balls mainly made of silicon nitride were used as the pulverization media. In addition, 1% by mass of ethanol was added as a pulverization aid just before the start of fine pulverization, and the pulverizer was sealed to perform fine pulverization. Then, the pulverizer was heated in air to perform an oxidation treatment, and the total oxygen concentration was adjusted to obtain silicon nitride powder A. The measurement results of the obtained silicon nitride powder A are shown in Table 1.
[0063] (Production of silicon nitride powder B) As silicon nitride powder B, a commercially available silicon nitride powder was heated in a nitrogen atmosphere to prepare the silicon nitride powder shown in Table 1.
[0064] (Production of silicon nitride powder C) Silicon nitride powder C was obtained in the same manner as in the production method of silicon nitride powder A, except that the oxidation treatment was not carried out. The measurement results of the obtained silicon nitride powder C are shown in Table 1. [Table 1]
[0065] <Sintering aid> 1. Compounds that do not have oxygen bonds The Y2Si4N6C powder was prepared by subjecting yttria (manufactured by Shin-Etsu Chemical Co., Ltd.), silicon nitride powder (the in-house powder described above), and carbon powder (manufactured by Mitsubishi Chemical) to thermal synthesis using the following reaction formula. 8Si3N4+6Y2O3+15C+2N2→6Y2Si4N6C+9CO2 Similarly, MgSi4N6C powder was prepared by thermal synthesis using the following reaction formula. Si3N4+MgSiN2+C→MgSi4N6C 2. Metal oxides Yttria (Y2O3) ··Manufactured by Shin-Etsu Chemical Co., Ltd.
[0066] <Binder> The binder used was a water-based resin binder, polyvinyl alcohol resin (Nippon Vinyl Acetate & Poval Corporation).
[0067] [Example 1] 100 parts by mass of silicon nitride powder A, 2 parts by mass of a compound Y2Si4N6C not containing an oxygen bond, 5 parts by mass of MgSi4N6C, and 3 parts by mass of yttria were weighed, and pulverized and mixed in a ball mill for 24 hours using a resin pot and silicon nitride balls with water as a dispersion medium. The water was weighed in advance so that the concentration of the slurry was 60 wt% and was put into the resin pot. After pulverization and mixing, 22 parts by mass of a water-based resin binder was added, and mixing was further carried out for 12 hours to obtain a slurry-like molding composition. Next, the viscosity of the molding composition was adjusted using a vacuum defoamer (manufactured by Sayama Riken) to prepare a coating slurry. Then, the viscosity-adjusted molding composition was sheet-formed by the doctor blade method to obtain a sheet molded body with a width of 75 cm and a thickness of 0.42 mmt. The sheet compact obtained as described above was degreased in dry air at a temperature of 550° C. to obtain a degreased compact. The physical properties of the obtained compact are shown in Table 2. The degreased green body was then placed in a sintering vessel and sintered at 1780°C for 9 hours in a nitrogen atmosphere under a pressure of 0.02 MPa·G to obtain a silicon nitride sintered body. The physical properties of the sintered body are shown in Table 2.
[0068] [Comparative Example 1] A silicon nitride sintered body was obtained in the same manner as in Example 1, except that the silicon nitride powder A used in Example 1 was changed to silicon nitride powder B. The physical properties of the sintered body are shown in Table 2.
[0069] [Example 2] A silicon nitride sintered body was obtained in the same manner as in Example 1, except that the amount of sintering aid was changed as shown in Table 2, the total oxygen amount and compact density were set as shown in Table 2, and the firing temperature was changed to 1740° C. The physical properties of the sintered body are shown in Table 2.
[0070] [Example 3] A silicon nitride sintered body was obtained in the same manner as in Example 1, except that silicon nitride powder C was used as the silicon nitride powder and the amount of sintering aid was adjusted to change the total oxygen amount and the compact density as shown in Table 2. The physical properties of the sintered body are shown in Table 2.
[0071] [Table 2]
[0072] As is clear from the results of each example, when a specific molded body is used, it is possible to obtain a sintered body with high thermal conductivity, even when the beta-conversion rate of the silicon nitride powder used as the raw material is high and the pressure during sintering is low. In contrast, when a molded body not satisfying the requirements of the present invention was used, a sintered body having high thermal conductivity could not be obtained when the sintering pressure was low.
Claims
1. The β-formation rate is 80% or more, the amount of dissolved oxygen is 0.1% by mass or less, the total oxygen amount is 1% by mass or more and 10% by mass or less, and the specific surface area is 5 to 20 m 2 / g silicon nitride powder; and a sintering aid containing a carbonitride compound containing a rare earth element or magnesium element as a compound having no oxygen bond, wherein the total oxygen content is adjusted to 1 to 15 mass % and the total aluminum content is 800 ppm or less, and the molded body is heated to a temperature of 1200 to 1800°C under an inert gas atmosphere and a pressure of 0 MPa G or more and less than 0.1 MPa G to sinter the silicon nitride.
2. 2. The method for producing a silicon nitride sintered body according to claim 1, wherein the molded body is obtained by molding a molding composition containing silicon nitride powder, a sintering aid, and water.
3. The silicon nitride powder has an average particle size D 50 3. The method for producing a silicon nitride sintered body according to claim 1, wherein the ratio of particles having a particle size of 0.5 μm or less is 20 to 50 mass %, and the ratio of particles having a particle size of 1.0 μm or more is 20 to 50 mass %.
4. The method for producing a silicon nitride sintered body according to any one of claims 1 to 3, wherein the sintering aid contains a metal oxide.
5. The density of the molded body is 1.95 g / cm 3 The method for producing a silicon nitride sintered body according to any one of claims 1 to 4, wherein
6. The method for producing a silicon nitride sintered body according to any one of claims 1 to 5, wherein the thermal conductivity of the resulting silicon nitride sintered body measured by a laser flash method is 80 W / mK or more.
7. The method for producing a silicon nitride sintered body according to any one of claims 1 to 6, wherein the resulting silicon nitride sintered body has a dielectric breakdown voltage of 11 kV or more.
8. The method for producing a silicon nitride sintered body according to any one of claims 1 to 7, wherein the silicon nitride sintered body obtained has an Ra of 0.6 µm or less.
Citation Information
Patent Citations
Silicon nitride powder
JP1991177307A
Production of silicon nitride powder
JP1998218612A
High thermal conductive silicon nitride ceramic and its manufacturing method
JP2002128569A
Manufacturing method of silicon nitride powder
JP2009161376A
Nitrogen and silicon-based sintered body and manufacturing method thereof
JP2015086125A
Cited By
Method of manufacturing green sheet
JPWO2022075156A1